UPAYA GURU DALAM MENGATASI PERILAKU BULLYING DI SEKOLAH STUDI KASUS MI NAHDLATUTH THULLAB GEDANGSARI - Ayjah Zukriah Romadhoni; Mahali, Muhamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the forms of bullying behavior and the efforts made by teachers to prevent and address bullying at MI Nahdlatuth Thullab Gedangsari, Gunungkidul. This research employed a qualitative approach with data collection techniques including non-participant observation, semi-structured interviews and documentation. The research informants consisted of the participal, theacers, the vice principal of student affairs dan students. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, with credibility testing out through source and technique triangulation. The findings revealed three fornms of bullying the school: verbal bullying (mocking, using harsh words, humiliating peers), physical bullying (pinching, hitting, pushing, pulling uniforms), and mental bullying (ostracizing, ignoring, showing cynical attitudes). Bullying behavior occurs due to several factors, including the influence of peers or the school environment, as well as the home environment and parenting styles. The preventive efforts implemented include the enforcement of pilice as standar operating procedures (SOP) for case handling, the establishment of an anti-bullying team, teacher and staff upgrading dan evaluation programs, antibullying socialization in collaboration with the police, the provision of educational media such as posters and wall magazines, habituation of religious practices, the implementation of reward and punishment systems, outing class activities, and intensive collaboration with parent. Supporting factors include cooperation with stakeholders, parents, and the Islamic boarding school environment that strengthens religious values. Meanwhile, inhibiting factors stem from differences in students’characters and family backgrounds. This study emphasizes that bullying prevention requires multidimensional approach involving schools, teachers and families in order to create a safe and conducive learning environment.